A rare presentation of mesenteric cystic lymphangioma in 5-year-old girl - Patrycja Sosnowska-Sienkiewicz; Cezary Miedziarek; Przemysław Mańkowski (Termedia Publishing House, 2021)
Acute abdominal pain is a frequent event in the paediatric population and appendicitis is the most common cause. Abdominal lymphangiomas occur most frequently in the mesenterium and are usually asymptomatic. Nevertheless, they can manifest as acute abdomen, needing surgical treatment. We report the case of a 5-year-old female operated on due to suspicion of acute abdomen. The pathological lesion was surgically removed during the second operation. The differential diagnosis of acute abdomen should be initially focused on the most common abdominal diseases. However, rare cases, like the presented one, must also be taken into consideration. Ultrasound examination plays important role in the initial differentiation of the causes of abdominal pain.